Spremembe v medčloveških odnosih v obdobju pomanjkanja in lakote (Ljubljana: 1914-1918) - Šorn, Mojca (Studia Historica Slovenica, 2020)
The following contribution, which focuses on Ljubljana and its inhabitants during World War I, shows how everyday life was influenced by the military and political as well as economic and social aspects. It underlines the food shortage, which did not only result in an increased incidence of diseases and deaths but also adjusted nutrition as well as modified daily rhythms and mental and psychological processes. The present contribution, which focuses on the interpersonal relationship changes in the extraordinary wartime circumstances or during the period of shortage and hunger, reveals that the code of behaviour as well as the established societal and social norms of the pre-war period often became a thing of the past.
Keywords: družbena kriza; economic circumstances; gospodarske razmere; hunger; lakota; Ljubljana; shortage; social interaction; svetovna vojna 1914-1918; World War I; zgodovina